Effect of the Equilibrium Pair Separation on Cluster Structures (Communications in Computational Physics, 2009)
The effect of the equilibrium pair separation on the evolution of clusterstructures is investigated based on a new proposed pair potential. The computationalresults demonstrate that the potential with large equilibrium pair separation stabilizesdecahedra and close-packed structures, while disordered structures appear for the potentialwith small equilibrium pair separation. The icosahedral clusters are dominatedin the middle range of equilibrium pair separation. For the small size clusters (N≤24)the dominated structural motif is the polytetrahedra, which is almost independent ofthe details of the potential.